2022 年全球气候状况 - World Meteorological Organization (United Nations, 2023)
The years 2015 to 2022 were the eight warmest in the 173-year instrumental record. Concentrations of the three main greenhouse gases – carbon dioxide, methane and nitrous oxide – reached record highs in 2021, the latest year for which consolidated global values are available (1984–2021). The annual increase in methane concentration from 2020 to 2021 was the highest on record. Real-time data from specific locations show that levels of the three greenhouse gases continued to increase in 2022. This report shows that, once again, greenhouse gas concentrations in the atmosphere continue to reach record levels – contributing to warming of the land and ocean, melting of ice sheets and glaciers, rising sea levels, and warming and acidifying of oceans. There are major gaps in the weather and climate observing networks, especially in the least developed countries (LDCs) and small island developing States (SIDS), which is an obstacle for climate baseline monitoring, especially at regional and national scales, and for the provision of early warning and adequate climate services. The United Nations Early Warnings for All Initiative, spearheaded by WMO, aims to fill the existing capacity gap to ensure that every person on Earth is covered by early warning services. Achieving this ambitious task requires sound observations and regular updates on key climate indicators, as provided in this report.